The Role of Islamic Boarding Schools in Preventing Radicalism in Polewali Mandar Regency - Sulkifli Sulkifli (Institut Agama Islam Negeri Kendari, 2023)
The objective of this research is to find out the role of Islamic boarding schools in preventing radicalism in Polewali Mandar Regency, West Sulawesi. This research is qualitative field research using a phenomenological-theological approach. This research was conducted in two Islamic boarding schools (Syekh Hasan Yamani and Salafiyah Parappe Islamic Boarding School) with data collection methods through observation, documentation, and interviews which were concluded through a general conclusion. The result of this research reveals that Islamic boarding schools in Polewali Mandar play an active role in preventing radicalism. The Prevention is carried out with two models, namely (1) inculcating moderate values in students through selecting reference books and selecting teaching staff, strengthening moderate values through curriculum, responsiveness to acts of terrorism, (2) inculcating a sense of nationalism in students through flag ceremonies, Civic Education learning, scouting activities carried out routinely by the Islamic boarding school